Transjugular liver biopsy: how good is it for accurate histological interpretation?. Issue 12 (24th April 2006) - Cholongitas, E; Quaglia, A; Samonakis, D; Senzolo, M; Triantos, C; Patch, D; Leandro, G; Dhillon, A P; Burroughs, A K
Abstract : Background: A transjugular liver biopsy (TJLB) specimen is often smaller or more fragmented than a percutaneous liver biopsy (PLB) specimen. Recently, for PLB, the minimum requirements to evaluate chronic hepatitis have been set at 20–25 mm length and ⩾11 complete portal tracts. Aim: To evaluate and compare length of TJLB and PLB specimens, portal tract number, fragmentation and adequacy for histopathological diagnosis and staging. Patients and methods: 326 consecutive TJLB specimens in 274 patients (109 who had undergone a transplantation), always using three passes (19-G Tru-cut) and 40 consecutive PLB specimens (15-G Menghini). Results: No technical failures occurred with the TJLB, and histological diagnosis was possible in 98.5%. The median (range) number of fragments was 5 (1–13) and the median total length was 22 (3–46) mm, with 65% of specimens ⩾20 mm and 36% ⩾25 mm; 60% of TJLB specimens were ⩾28 mm long had ⩾11 complete portal tracts. No difference in complete portal tract number or biopsy length was found between PLB and TJLB specimens. Conclusion: A TJLB specimen with three passes is adequate for histological diagnosis, with 89% of specimens being either ⩾15 mm or having ⩾6 complete portal tracts. Although adequate sampling remains a limitation for staging and grading of chronic hepatitis, TJLB is comparable to PLB in this respect.